Problem Solving and Experimentation implemented in Natural Science classes in a Ninth year class of Basic Education (Research, Society and Development, 2022)
The present study brings an excerpt of a work implemented in Basic Education on Resolution and Problems and Experimentation that was developed with a class of Ninth Year of Elementary School of a municipal school of education, located in the urban area of Caçapava do Sul, RS. As a general objective, it is expected to verify whether learning can be favored through the articulation of Problem Solving and Experimentation methodologies, thus seeking to improve teaching and learning processes and better understanding of the contents developed in the area of Natural Sciences. Qualitative research was used and data were produced through audio recordings of classes, fron the seminars and analysis of reports. As a methodological instrument for analysis of results, Bardin's Content Analysis was used. As a result it is pointed out that students agree to have a better learning using the presented methodologies. It can be seen that from this work, the students felt more curious in the sense of deepening their knowledge and even understanding concepts that they had not understood before.